Xanthophyll cycle-related non-photochemical quenching protects Sargassum thunbergii from high light-induced photoinhibition - Guo-Ning Nan; Xiao-Qun Zhou; Xiu-Mei Zhang; Quan-Sheng Zhang; Zi-Min Hu; Rui-Ping Huang; Di Zhang (Frontiers in Marine Science, 2022)
As a common macroalga living in the intertidal zone, Sargassum thunbergii (Sargassaceae, Phaeophyta) is often exposed to drastic changes in solar photosynthetically active radiation during a diurnal cycle; thus, the potential photosynthetic adaptation processes deserve attention. In this work, we examined the photosynthetic performance and xanthophyll cycle activity of this alga in response to high light (1,200 μmol photons m–2 s–1, the average in-situ light intensity at noon) by using chlorophyll fluorescence and high-performance liquid chromatography (HPLC). On exposure to high light, a rapid decrease in the effective quantum yield of photosystem II (PSII) (Y(II)) occurred, indicating down-regulation of PSII activity; a corresponding increase in non-photochemical quenching (NPQ) indicated the existence of energy-dissipating cycles. After turning off the light, Y(II) gradually increased to 0.7, accompanied by a decrease in NPQ. However, no complete recovery of NPQ was observed, and its value remained at ≈4, even after an 80-min dark treatment. The size of the xanthophyll cycle pigments pool was quantified using HPLC and was found to be ≈16 mol mol−1 Chl a × 100. The activity of the xanthophyll cycle, characterized by a de-epoxidation state (DPS), could reach up to ≈0.5. Such a large pigments pool and rapid accumulation of zeaxanthin may allow S. thunbergii to induce high values of NPQ (≈10). These results were further complemented by inhibitor (dithiothreitol, DTT) and pre-illumination experiments showing that (1) both NPQ and the xanthophyll cycle could be inhibited by DTT, and there was always a strong positive correlation between NPQ and DPS; (2) the previously formed antheraxanthin exhibited a long retention time and a slow epoxidation; and (3) the long retention of antheraxanthin contributed to a rapid accumulation of zeaxanthin. In conclusion, our present study demonstrated that xanthophyll cycle-induced NPQ can significantly protect S. thunbergii from light fluctuations in the intertidal zone.